Large carnivores avoid humans while prioritizing prey acquisition in anthropogenic areas. Issue 4 (17th February 2023) - Barker, Kristin J.; Cole, Eric; Courtemanch, Alyson; Dewey, Sarah; Gustine, David; Mills, Kenneth; Stephenson, John; Wise, Benjamin; Middleton, Arthur D.
Abstract: Large carnivores are recovering in many landscapes where the human footprint is simultaneously growing. When carnivores encounter humans, the way they behave often changes, which may subsequently influence how they affect their prey. However, little research investigates the behavioural mechanisms underpinning carnivore response to humans. As a result, it is not clear how predator–prey interactions and their associated ecosystem processes will play out in the human‐dominated areas into which carnivore populations are increasingly expanding. We hypothesized that humans would reduce predation risk for prey by disturbing carnivores or threatening their survival. Alternatively, or additionally, we hypothesized that humans would increase predation risk by providing forage resources that congregate herbivorous prey in predictable places and times. Using grey wolves Canis lupus in Jackson Hole, Wyoming, USA as a study species, we investigated 170 kill sites across a spectrum of human influences ranging from heavily restricted human activities on protected federal lands to largely unregulated activities on private lands. Then, we used conditional logistic regression to quantify how the probability of predation changed across varied types and amounts of human influences, while controlling for environmental characteristics and prey availability. Wolves primarily made kills in environmental terrain traps and where prey availability was high, but predation risk was significantly better explained with the inclusion of human influences than by environmental characteristics alone. Different human influences had different, and even converse, effects on the risk of wolf predation. For example, where prey were readily available, wolves preferentially killed animals far from motorized roads but close to unpaved trails. However, wolves responded less strongly to humans, if at all, where prey were scarce, suggesting they prioritized acquiring prey over avoiding human interactions. Overall, our work reveals that the effects of large carnivores on prey populations can vary considerably among different types of human influences, yet carnivores may not appreciably alter predatory behaviour in response to humans if prey are difficult to obtain. These results shed new light on the drivers of large carnivore behaviour in anthropogenic areas while improving understanding of predator–prey dynamics in and around the wildland–urban interface. Abstract : Using a novel dataset of wolf kill site investigations, this work reveals that failing to account for human influences significantly reduces the ability to explain patterns of wolf predation on native ungulates. However, wolves may not appreciably alter predatory behaviour in response to humans in areas where prey are scarce.